Management and clinical outcomes of type I gastric carcinoid patients: Retrospective, multicenter study in Japan. Issue 3 (5th November 2013) - Sato, Yuichi; Imamura, Hiroshi; Kaizaki, Yasuharu; Koizumi, Wasaburo; Ishido, Kenji; Kurahara, Koichi; Suzuki, Haruhisa; Fujisaki, Junko; Hirakawa, Katsuya; Hosokawa, Osamu; Ito, Masanori; Kaminishi, Michio; et al.
Abstract : Background and Aim: Type I gastric carcinoids (TIGC) are associated with chronic atrophic gastritis (CAG) with hypergastrinemia and hyperplasia of enterochromaffin‐like cells. Several treatment options are currently available for these tumors including total gastrectomy, partial resection, antrectomy, endoscopic resection and endoscopic surveillance. The present study evaluated different treatment approaches and clinical outcomes of patients with TIGC in Japan. Methods: Between 1991 and 2011, 82 patients with TIGC were identified at multicenter institutions in Japan. Patient demographics, tumor size, depth of invasion, vessel involvement, treatment approach, Helicobacter pylori infection, serum gastrin level, recurrence‐free survival (RFS) and disease‐specific survival (DSS) were analyzed. Results: Median age of all patients at the time of diagnosis was 56 years (range, 24−79 years). There were 44 males and 38females. Patients underwent endoscopic surveillance ( n  = 25), endoscopic resection ( n  = 41) or surgical resection ( n  = 16). Intramucosal invasion was found in 19 patients, submucosal invasion in 44 patients and muscularis propria invasion in one patient. Tumor diameter was ≤10 mm in 71 patients, 11–20 mm in five patients and ≥21 mm in five patients. None of the patients showed rapidly growing tumors, local recurrence or metastasis. The median (range) follow‐up period was 7 (0–20) years. RFS was 97.6% and DSS was 100% in all the patients. Conclusion: The prognosis of TIGC patients treated by different modalities in Japan is favorable regardless of the generational change of management for TIGC.